Phylogeography and evolutionary history of the Crocidura olivieri complex (Mammalia, Soricomorpha): from a forest origin to broad ecological expansion across Africa - Jacquet, François; Denys, Christiane; Verheyen, Erik; Bryja, Josef; Hutterer, Rainer; Kerbis Peterhans, Julian C; Stanley, William T; Goodman, Steven M; Couloux, Arnaud; Colyn, Marc; Nicolas, Violaine (BMC evolutionary biology, 2015)
BACKGROUND: This study aims to reconstruct the evolutionary history of African shrews referred to the Crocidura olivieri complex. We tested the respective role of forest retraction/expansion during the Pleistocene, rivers (allopatric models), ecological gradients (parapatric model) and anthropogenic factors in explaining the distribution and diversification within this species complex. We sequenced three mitochondrial and four nuclear markers from 565 specimens encompassing the known distribution of the complex, i.e. from Morocco to Egypt and south to Mozambique. We used Bayesian phylogenetic inference, genetic structure analyses and divergence time estimates to assess the phylogenetic relationships and evolutionary history of these animals. RESULTS: The C. olivieri complex (currently composed of C. olivieri, C. fulvastra, C. viaria and C. goliath) can be segregated into eight principal geographical clades, most exhibiting parapatric distributions. A decrease in genetic diversity was observed between central and western African clades and a marked signal of population expansion was detected for a broadly distributed clade occurring across central and eastern Africa and portions of Egypt (clade IV). The main cladogenesis events occurred within the complex between 1.37 and 0.48 Ma. Crocidura olivieri sensu stricto appears polyphyletic and C. viaria and C. fulvastra were not found to be monophyletic. CONCLUSIONS: Climatic oscillations over the Pleistocene probably played a major role in shaping the genetic diversity within this species complex. Different factors can explain their diversification, including Pleistocene forest refuges, riverine barriers and differentiation along environmental gradients. The earliest postulated members of the complex originated in central/eastern Africa and the first radiations took place in rain forests of the Congo Basin. A dramatic shift in the ecological requirements in early members of the complex, in association with changing environments, took place sometime after 1.13 Ma. Some lineages then colonized a substantial portion of the African continent, including a variety of savannah and forest habitats. The low genetic divergence of certain populations, some in isolated localities, can be explained by their synanthropic habits. This study underlines the need to revise the taxonomy of the C. olivieri complex.
Keywords: Genetic Speciation; Ecosystem; genetická variace; Bayes Theorem; fylogeneze; rejskovití; Forests; Phylogeny; Afrika; Ecology; biologická evoluce; Phylogeography; vznik druhů (genetika); genetický drift; Animals; Africa; Biological Evolution; ekologie; zvířata; fylogeografie; Bayesova věta; ekosystém; Genetic Drift; Shrews; lesy; Genetic Variation